THE SOCIAL MODELS OF THE OFFENDER'S PERSONALITY FORMATION - G. Gumirova (Russian Journal of Economics and Law)
The article views the social models of the adolescents' deviant behavior and offender's personality formation. All of them, according to the author, are to certain extent connected with the unfairness in the family, microenvironment or society as a whole, which should be taken into account during the study of the personality and reformation of its views and behavioral standards.